E-business and e-commerce management strategy, implementation and practice - Chaffey, Dave 1963- (Harlow, England New York FT Prentice Hall, 2009)
This volume covers business models, theoretical tools and international aspects of e-business and e-commerce.
Includes bibliographical references and index.
Tac-3002g donated by UPAA Netherlands on June 24, 2015.
Keywords: Electronic commerce; Business enterprises -- Computer networks